Activation of WNT signaling restores the facial deficits in a zebrafish with defects in cholesterol metabolism. Issue 12 (16th November 2020) - Castro, Victoria L.; Reyes‐Nava, Nayeli G.; Sanchez, Brianna B.; Gonzalez, Cesar G.; Paz, David; Quintana, Anita M.
Summary: Inborn errors of cholesterol metabolism occur as a result of mutations in the cholesterol synthesis pathway (CSP). Although mutations in the CSP cause a multiple congenital anomaly syndrome, craniofacial abnormalities are a hallmark phenotype associated with these disorders. Previous studies have established that mutation of the zebrafish hmgcs1 gene (Vu57 allele), which encodes the first enzyme in the CSP, causes defects in craniofacial development and abnormal neural crest cell (NCC) differentiation. However, the molecular mechanisms by which the products of the CSP disrupt NCC differentiation are not completely known. Cholesterol is known to regulate the activity of WNT signaling, an established regulator of NCC differentiation. We hypothesized that defects in cholesterol synthesis are associated with reduced WNT signaling, consequently resulting in abnormal craniofacial development. To test our hypothesis we performed a combination of pharmaceutical inhibition, gene expression assays, and targeted rescue experiments to understand the function of the CSP and WNT signaling during craniofacial development. We demonstrate reduced expression of four canonical WNT downstream target genes in homozygous carriers of the Vu57 allele and reduced axin2 expression, a known WNT target gene, in larvae treated with Ro‐48‐8071, an inhibitor of cholesterol synthesis. Moreover, activation of WNT signaling via treatment with WNT agonist I completely restored the craniofacial defects present in a subset of animals carrying the Vu57 allele. Collectively, these data suggest interplay between the CSP and WNT signaling during craniofacial development.